1986
DOI: 10.1104/pp.82.4.1051
|View full text |Cite
|
Sign up to set email alerts
|

The Uptake of NO3, NO2, and NH4+ by Intact Wheat (Triticum aestivum) Seedlings

Abstract: The inducibility and kinetics of the NO3-, NO2-, and NH4+ transporters in roots of wheat seedlings (Triticum aestivum cv Yercora Rojo) were characterized using precise methods approaching constant analysis of the substrate solutions. A microcomputer-controlled automated high performance liquid chromatography system was used to determine the depletion of each N species (initially at 1 millimolar) from complete nutrient solutions. Uptake rate analyses were performed using computerized curve-fitting techniques. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
60
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 21 publications
11
60
1
Order By: Relevance
“…This model conformed best with the measured data with regard to the obtained standard errors (data not shown) and the fitting of curves to the means of uptake rates (Fig. 3) Aslam et al 1992), but lower than those found in maize (24 mmol m -3 , Hole et al 1990), in wheat (27 mmol m -3 , Goyal & Huffaker 1986b) and in Arabidopsis (40 mmol m -3 , Doddema & Telkamp 1979) or in excised barley roots in earlier reports (110 mmol m -3 , Rao & Rains 1976a). Similar agreements were found for the 13 N-NO 3 -influx (Lee & Drew 1986: 14 mmol m -3 ;Siddiqi et al 1990: between 30 and 79 mmol m -3 depending on the N status of the plants).…”
Section: Kinetic Parametersmentioning
confidence: 49%
See 1 more Smart Citation
“…This model conformed best with the measured data with regard to the obtained standard errors (data not shown) and the fitting of curves to the means of uptake rates (Fig. 3) Aslam et al 1992), but lower than those found in maize (24 mmol m -3 , Hole et al 1990), in wheat (27 mmol m -3 , Goyal & Huffaker 1986b) and in Arabidopsis (40 mmol m -3 , Doddema & Telkamp 1979) or in excised barley roots in earlier reports (110 mmol m -3 , Rao & Rains 1976a). Similar agreements were found for the 13 N-NO 3 -influx (Lee & Drew 1986: 14 mmol m -3 ;Siddiqi et al 1990: between 30 and 79 mmol m -3 depending on the N status of the plants).…”
Section: Kinetic Parametersmentioning
confidence: 49%
“…The HATS is described as a saturable system, whereas the nature of the LATS is still not clear. Doddema & Telkamp (1979) and Goyal & Huffaker (1986b) found a second saturable system, but Siddiqi et al (1990) and Aslam, Travis & Huffaker (1992) observed a linear non-saturable component under higher concentrations of nitrate. Aslam et al (1992) even found two saturable, possibly constitutive systems in the low concentration range and a linear system at more than 500 mmol m -3 nitrate.…”
Section: Introductionmentioning
confidence: 99%
“…The induction of the Nos-and NOz-uptake systems in the presence of their respective substrates is well established (Jackson et al, 1973(Jackson et al, , 1974a(Jackson et al, , 1974bGoyal and Huffaker, 1986b;Aguera et al, 1990;Siddiqi et al, 1990). In addition, both uptake systems clearly appear to be induced by Nos- (Aslam et al, 1992a).…”
mentioning
confidence: 75%
“…The available data indicate that entry of NH' and NO-into roots apparently is mediated by more than one transporter specific for each ion (11,36). To dissect nitrogen transport systems at the molecular level, genes encoding putative transporters for mineral nitrogen were cloned.…”
Section: Discussionmentioning
confidence: 99%